2019
DOI: 10.1038/s41419-019-1755-2
|View full text |Cite
|
Sign up to set email alerts
|

EZH2, JMJD3, and UTX epigenetically regulate hepatic plasticity inducing retro-differentiation and proliferation of liver cells

Abstract: Modification of histones by lysine methylation plays a role in many biological processes, and it is dynamically regulated by several histone methyltransferases and demethylases. The polycomb repressive complex contains the H3K27 methyltransferase EZH2 and controls dimethylation and trimethylation of H3K27 (H3K27me2/3), which trigger gene suppression. JMJD3 and UTX have been identified as H3K27 demethylases that catalyze the demethylation of H3K27me2/3, which in turns lead to gene transcriptional activation. EZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The cells were harvested, fixed in chilled 70% ethanol, treated with RNase A (100 μg/ml RNase) for 15 min at 37 °C and stained with propidium iodine (PI) (10 μg/ml PI) as described 35 . Data acquisition and analysis was carried out using a flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were harvested, fixed in chilled 70% ethanol, treated with RNase A (100 μg/ml RNase) for 15 min at 37 °C and stained with propidium iodine (PI) (10 μg/ml PI) as described 35 . Data acquisition and analysis was carried out using a flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…JMJD3 is involved in cellular processes including differentiation, proliferation, senescence, and apoptosis, and thus is implicated in development and diseases 23 . JMJD3, UTX and EZH2 regulate hepatic plasticity inducing retro-differentiation and proliferation of hepatocytes 24 . In the setting of SSc, JMJD3, but not UTX, is overexpressed in SSc and murine models of skin fibrosis as well as in cultured fibroblasts, modulates fibroblast activation by regulating H2K27me3 content at FRA2 gene promoter, which encodes the AP1 transcription factor that regulates ECM production.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancer of zeste homolog 2 (EZH2) protein is the core catalytic element of polycomb repressor complex 2 (PRC2), which regulates the transcription of target genes via promoting histone H3 methylation ( 11 13 ). Previous studies have demonstrated that high expression level of EZH2 is a poor prognostic factor in various types of cancer ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%